The Effect of Dexmedetomidine on Postoperative Nausea and Vomiting in Patients Undergoing Thoracic Surgery-A Meta-Analysis of a Randomized Controlled Trial - Zhang, Wei; Wang, Ruohan; Li, Bing; Zhao, Ying; Liu, Xinmin; Yuan, Jingli (Frontiers in Surgery, 2022)
Abstract Background: Dexmedetomidine reduces the occurrence of postoperative nausea and vomiting (PONV); however, the effect of dexmedetomidine on PONV in patients undergoing thoracic surgery remains inconclusive. In addition, the effect of different dexmedetomidine application methods, anesthetics and surgical procedures on the effects of dexmedetomidine on PONV remain unclear. Therefore, the purpose of this meta-analysis was to study the effect of dexmedetomidine on PONV in patients undergoing thoracic surgery. Methods: Electronic databases were searched to identify randomized controlled trials studying the effects of dexmedetomidine on nausea and vomiting after thoracic surgery. In total, twelve articles that met the inclusion criteria were obtained. The primary outcome of this comprehensive analysis was the incidence of PONV; secondary outcomes included the incidence of postoperative nausea, the incidence of postoperative vomiting, postoperative visual analogue score (VAS), the amount of intraoperative sufentanil, and the number of times postoperative salvage analgesia was administered. Results: Twelve trials involving 905 participants undergoing thoracic surgery were included. Compared with placebo, dexmedetomidine reduced the incidence of nausea and vomiting after thoracic surgery (12 trials; 905 participants; risk ratio (RR) = 0.32; 95% confidence interval (CI) [0.23, 0.44]; P < 0.00001, I2 = 0%). Subgroup analysis revealed that dexmedetomidine reduces the occurrence of PONV in both thoracotomy and thoracoscopic surgery. In addition, both intravenous and local infusion of dexmedetomidine can reduce the occurrence of PONV, and intravenous or inhaled anesthetics do not affect the effect of dexmedetomidine on reducing PONV. Dexmedetomidine can reduce the postoperative resting visual analog score (VAS) of patients, and no statistically significant differences in the amount of intraoperative sufentanil and the number of salvage analgesia procedures after surgery were noted. Conclusions: Compared with placebo, dexmedetomidine can reduce the occurrence of PONV in patients undergoing thoracic surgery, and this effect is not affected by the method of dexmedetomidine administration, use of minimally invasive surgery, and use of a combination of intravenous or inhalation anesthetics.